The Bilingual Counselor's Guide to Spanish : Basic Vocabulary and Interventions for the Non-Spanish Speaker. - Swazo, Roberto (Taylor and Francis, 2013)
Designed specifically with mental health professionals in mind, The Bilingual Counselor's Guide to Spanish is perfect for counselors interested in expanding their client base and language skill set. Featuring terminology and cultural phrases specific to the mental health profession, this text offers an easy introduction to both the Spanish language and interfacing with Spanish-speaking clients in a counseling setting. Sections of useful and practical vocabulary are followed by ¡Practique! sections, which enable to reader to put his or her developing skills to use. These sect.